Chua Ek Kay After the Rain - Low, Sze Wee (National Gallery Singapore, 2015)
Chua Ek Kay is regarded as one of Singapore's leading ink practitioners, celebrated for his distinctive visual vocabulary that bridges Chinese ink painting traditions and Western aesthetics. After the Rain is the first major survey of Chua, covering over three decades of his prolific practice. This catalogue includes essays that illuminate Chua's approaches to ink painting and underscore his contributions to its development in Singapore. It also features a heretofore unpublished manuscript interview byChua, discovered posthumously in his study, as well as reflections by Mrs Chua Ek Kay. A biographical timeline produced in consultation with Chua's family further enhances the presentation of his work.